Loop-Mediated Isothermal Amplification for Detection of African Trypanosomes - Kuboki, Noritaka (American Society for Microbiology, 2003)
While PCR is a method of choice for the detection of African trypanosomes in both humans and animals, the expense of this method negates its use as a diagnostic method for the detection of endemic trypanosomiasis in African countries. The loop-mediated isothermal amplification (LAMP) reaction is a method that amplifies DNA with high specificity, efficiency, and rapidity under isothermal conditions with only simple incubators. An added advantage of LAMP over PCR-based methods is that DNA amplification can be monitored spectrophotometrically and/or with the naked eye without the use of dyes. Here we report our conditions for a highly sensitive, specific, and easy diagnostic assay based on LAMP technology for the detection of parasites in the Trypanosoma brucei group (including T. brucei brucei, T. brucei gambiense, T. brucei rhodesiense, and T. evansi) and T. congolense. We show that the sensitivity of the LAMP-based method for detection of trypanosomes in vitro is up to 100 times higher than that of PCR-based methods. In vivo studies in mice infected with human-infective T. brucei gambiense further highlight the potential clinical importance of LAMP as a diagnostic tool for the identification of African trypanosomiasis.